If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -5) = 2(x + 7) Reorder the terms: 5(-5 + x) = 2(x + 7) (-5 * 5 + x * 5) = 2(x + 7) (-25 + 5x) = 2(x + 7) Reorder the terms: -25 + 5x = 2(7 + x) -25 + 5x = (7 * 2 + x * 2) -25 + 5x = (14 + 2x) Solving -25 + 5x = 14 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -25 + 5x + -2x = 14 + 2x + -2x Combine like terms: 5x + -2x = 3x -25 + 3x = 14 + 2x + -2x Combine like terms: 2x + -2x = 0 -25 + 3x = 14 + 0 -25 + 3x = 14 Add '25' to each side of the equation. -25 + 25 + 3x = 14 + 25 Combine like terms: -25 + 25 = 0 0 + 3x = 14 + 25 3x = 14 + 25 Combine like terms: 14 + 25 = 39 3x = 39 Divide each side by '3'. x = 13 Simplifying x = 13
| 7+x-3=6+x | | 2(y-6x)=12 | | 6=n+24-8 | | 5-1/4y=10x | | (11x^8/8q^6)*(64q^8/121x) | | 7.5-y=43/4 | | 0=x^2-13x-30 | | 2r+16=1r-25 | | -6(r+7)=-90 | | 20=y-8.1 | | 2x-250=100 | | 9.16515139= | | 5a/5 | | 40+14d=2(-4d-13) | | 8.1+4=20 | | 2x+250=1000 | | 92+78+x=180 | | 49+x+3=90 | | x^2=-1/6 | | 8x-8=10x+7 | | -5x-6y=8 | | 1x+10=7t-14 | | 5(7x-8)=-329 | | 4x^4=324 | | 10000=6x+20 | | 10,000=6x+20 | | 6x+3=92 | | y-4=4(x-1) | | 5+2x=32 | | 3w-6=4.9 | | 3x+6=92 | | 0.28=ln(y) |